On new characterization of inextensible flows of space-like curves in de Sitter space - Yeneroglu, Mustafa (De Gruyter Poland Sp Zoo, 2016)
Elastica and inextensible flows of curves play an important role in practical applications. In this paper, we construct a new characterization of inextensible flows by using elastica in space. The inextensible flow is completely determined for any space-like curve in de Sitter space S-1(3). Finally, we give some characterizations for curvatures of a space-like curve in de Sitter space S-1(3).
Keywords: Fluid flow; Minkowski space-time; Partial differential equation; de Sitter space S-1(3)